Effects of landing height on lower extremity joint biomechanics during unilateral and bilateral landings - Koh, Y. C.; Cho, J. H.; Lee, H. D.; Lee, S. C. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to examine the lower extremity kinematics and kinetics during landing phase, in response to the effects of landing height during unilateral and bilateral landing. Ten young healthy male subjects (age: 26.1±1.8yr, height: 183.2±4.4cm, weight: 76.1±6.9kg) participated in this study. Each subject performed the unilateral and bilateral landing from a 30cm and 45cm wooden platform. The results showed the peak vertical ground reaction force (PVGRF) was increased during unilateral landing and at greater landing height (p <0.05). The knee joint valgus angles were elevated during bilateral landing, the knee joint valgus moment were higher during unilateral landing than bilateral landing (p <0.05). Based on our findings, to minimize the PVGRF and the valgus moment at the knee joint, bilateral landing is recommended for landing maneuvers.